PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION AUDITOR - Alifattiin Andar Murdani; Fachrurrozie Fachrurrozie (Pusat Riset dan Inovasi Nasional, 2022)
This research has a purpose to test the influence of job satisfaction and commitment of organization to the turnover intention. The population of this study are auditors who work at the Public Accounting Firm in Semarang City. The data used is primary data, with data collection techniques by distributing questionnaires. Determination of the sample is done using the conviniance sampling method, and obtained as many as 55 respondents. The data analysis method used is the multiple linear analysis method using the IMB SPSS Statistics 22 software.The results of the study explain that job satisfaction has a positive effect on turnover intention. Organizational commitment also has a positive effect on turnover intention. Likewise, job satisfaction and organizational commitment have a simultan effect on turnover intention.Based on the research, it can be concluded that the satisfaction of working and commitment of organization is partly positive for Turnover Inention auditors, while the satisfaction of work and commitment of the auditor's turnover intention. The lack of this research is the research has been the setback of previous research. Therefore the advice for the next researcher is expected to add a variable moderating or intervention that encourages variable turnover intention.